2017
DOI: 10.5935/1518-0557.20170005
|View full text |Cite
|
Sign up to set email alerts
|

Does oval oocyte have an impact on embryo development in in vitro fertilization?

Abstract: ObjectiveTo compare the outcomes of embryo development between oval-shaped oocyte as an abnormal morphology oocyte and a normal morphology oocyte in In Vitro Fertilization (IVF).MethodsThis study was a comparative analytical study with retrospective approach which lasted from September 2014 until November 2015. For this study, we used secondary data (medical records) from 24 patients submitted to IVF at the Halim Fertility Center. The oocyte morphology was divided into two groups: normal-shaped oocyte and oval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 18 publications
0
6
0
2
Order By: Relevance
“…Halim et al in their research compared normal and oval shaped oocytes in ICSI and found 46.7% transferrable embryos in the oval oocytes group compared to 63.3% in the normal oocytes group. However, there was no significant difference in fertilization rates and embryo quality between normal morphology oocytes and oval-shaped oocytes, but with a higher percentage towards the normal shaped oocytes [27].…”
Section: Discussionmentioning
confidence: 68%
“…Halim et al in their research compared normal and oval shaped oocytes in ICSI and found 46.7% transferrable embryos in the oval oocytes group compared to 63.3% in the normal oocytes group. However, there was no significant difference in fertilization rates and embryo quality between normal morphology oocytes and oval-shaped oocytes, but with a higher percentage towards the normal shaped oocytes [27].…”
Section: Discussionmentioning
confidence: 68%
“…Cumulus cells are not included, as these are removed according to the Open Cryotop ® user manual [20]. Only uniform samples are considered, as deviation from a spherical shape is considered a form of dysmorphia [14]. The choice of 0.1mm is a conservative size estimate, and accounts for loss of water volume and artificial collapse during the vitrification process.…”
Section: Liquid Nitrogen Is a Stationary Isothermal Liquidmentioning
confidence: 99%
“…Cumulus cells are not included, as these are required to be removed according to the Open Cryotop ® user manual [17]. Uniform embryos are considered, as deviation from a spherical shape is considered a form of dysmorphia [24]. The choice of 0.1mm is a conservative size estimate, and accounts for loss of water volume and artificial collapse during the vitrification process.…”
Section: Liquid Nitrogen Is a Stationary Isothermal Liquidmentioning
confidence: 99%